The decrease in the importance of land rent in the long run and its consequences - Czyżewski, Bazyli; Staniszewski, Jakub (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
The article develops the thesis of Thomas Piketty by distinguishing land from the general aggregate of capital resources, and then by comparing the growth rate of the land rent with the rate of growth of the incomes of the other production factors. The study of long-term trends in Italy, Spain, Great Britain, Germany, France, Denmark and Poland identified common to the most of these countries process of land rent regression, which carries a number of negative consequences, such as land-grabbing, unsustainability of the production processes in agriculture, and the relative deterioration of the situation of farmers. The occurrence of these phenomena associated with the regression of ground rent, caused by market mechanism, justifies the need for adjustment instruments in the form of the agricultural policy tools.
Keywords: agriculture; land rent; capital